RATIO LEGIS TERHADAP MUTASI PEGAWAI NEGERI SIPIL BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2023 TENTANG APARATUR SIPIL NEGARA - Apriani Apriani (Universitas Borneo Tarakan, 2025)
Job mutation plays an important role in managing human resources to improve performance, professionalism, and organizational effectiveness. In the public sector, mutation serves as a strategic instrument to maintain harmonious working relationships and prevent work stagnation among civil servants. This study examines the legal status of civil servant mutation and its ratio legis based on Law Number 20 of 2023 concerning the State Civil Apparatus, with a focus on its implementation within the Government of North Kalimantan Province. This research employs normative legal methods using statutory and conceptual approaches, supported by primary and secondary legal materials. The findings show that civil servant mutation is regulated under Law Number 5 of 2014, further elaborated in Government Regulation Number 11 of 2017 and regulations of the National Civil Service Agency. The ratio legis of mutation emphasizes procedural compliance and the application of a merit-based system to ensure professionalism and legal certainty in civil service management.